2013
DOI: 10.1073/pnas.1300579110
|View full text |Cite
|
Sign up to set email alerts
|

Surviving rapid climate change in the deep sea during the Paleogene hyperthermals

Abstract: Predicting the impact of ongoing anthropogenic CO 2 emissions on calcifying marine organisms is complex, owing to the synergy between direct changes (acidification) and indirect changes through climate change (e.g., warming, changes in ocean circulation, and deoxygenation). Laboratory experiments, particularly on longer-lived organisms, tend to be too short to reveal the potential of organisms to acclimatize, adapt, or evolve and usually do not incorporate multiple stressors. We studied two examples of rapid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 38 publications
6
54
0
Order By: Relevance
“…6b). Our models similarly reveal a strong size dependency in volumenormalised approaches, such as that used by Foster et al (2013) across the PETM. All model runs predict that the foraminiferal calcite volume / total volume ratio exhibits a strong dependence on test size (Fig.…”
Section: Implications For Size-normalised Weight (Snw) In Foraminifermentioning
confidence: 62%
See 2 more Smart Citations
“…6b). Our models similarly reveal a strong size dependency in volumenormalised approaches, such as that used by Foster et al (2013) across the PETM. All model runs predict that the foraminiferal calcite volume / total volume ratio exhibits a strong dependence on test size (Fig.…”
Section: Implications For Size-normalised Weight (Snw) In Foraminifermentioning
confidence: 62%
“…While there are as yet few data from smaller species of planktonic foraminifera and early ontogenetic stage individuals of larger planktonic foraminiferal species, there are some lines of evidence from small benthic foraminifera that could support the inverse calcification response that we propose. Foster et al (2013) found that small benthic foraminifera became more heavily calcified during the PETM, when ocean pH was lower (Penman et al, 2014). By contrast, during the high pH "carbonate overshoot" in the aftermath of the event (Penman et al, 2016), these foraminifera displayed thinner walls .…”
Section: Towards Understanding the Differential Response Of Foraminifmentioning
confidence: 95%
See 1 more Smart Citation
“…Those benthic foraminiferal species surviving the PETM had the ability to enhance their calcification relative to body volume (Foster et al . ). Intriguingly, deep sea ostracods show highly variable responses, some of which suggest that the climate change impacted the assemblages negatively (Steineck & Thomas ) while others suggest little change (Webb et al .…”
Section: Rapid Climate Change: Palaeogene Hyperthermalsmentioning
confidence: 97%
“…; PETM: (Foster et al . ). While there was extinction during the PETM (Thomas ), there is currently no evidence for climate‐related extinction in the marine record.…”
mentioning
confidence: 97%